The influence of mathematical disposition and gender on the numerical ability of Grade X students of SMAN 1 Bae Kudus - Mutiara, Sela; Wahyuni, Fina Tri (Universitas Ahmad Dahlan, 2023)
The background of this study is the lack of mathematical disposition of students and different genders towards the numerical abilities of class X students of SMAN 1 Bae Kudus. This study aims to (1) determine the influence of mathematical disposition on the numerical abilities of class X students of SMAN 1 Bae Kudus; (2) knowing the influence of gender on the numerical ability of class X students of SMAN 1 Bae Kudus; (3) knowing the influence of mathematical and gender dispositions together on the numerical abilities of class X students of SMAN 1 Bae Kudus. The types and approaches of research used are correlation and quantitative. This study was conducted in class XE8 involving 32 students. The results showed that: (1) there was a positive and significant influence of mathematical disposition on numerical ability with a significant contribution of 0.000 < from 0.05, (2) there was no positive and significant influence of gender on numerical ability because the significance value was 0.975 > 0.05, and (3) there is a positive influence and the significant mathematical disposition and gender together to the numerical ability of significance values of 0.000 < 0.05 and a percentage of 61.1%.